Empirical investigation into market power, markups and employment - Vladimír Peciar (Masaryk University, Faculty of Economics and Administration, 2021)
In this paper I use the production function approach popularized by De Loecker et al. (2020) to analyze the evolution of market power in Slovakia and some of its micro and macro implications. In contrast to other studies, I calculate markups from both value added and sales and empirically test whether some of the global trends in market power can be seen in Slovak firm level data as well. I find that the markups in Slovakia in fact declined since 2010, both in terms of value added and sales. Although the decrease in sales markups is negligible, the value added aggregate markup declined by 25% from 2.35 in 2012 to 1.78 in 2018. Value added markups tend to be higher for relatively value-added larger firms and they are also higher in larger sectors. Smaller firms (size indicated by number of employees) tend to have higher markups. It seems that a typical high markup firm is relatively small (in terms of number of employees) but produces relatively larger output. Correlations between markups and various measures of profitabality show that there is indeed a relationship between markups and market power. Markups strongly correlate with profits and they do not significantly react to changes in costs. Markups in Slovakia evolve in excess of marginal costs. Slovak firm data shows that markups are also inversely associated to labor shares. Correlation is statistically strong and empirically well established.
Keywords: D22; L11; 330; markups; market power; firm data